2012
DOI: 10.1073/pnas.1214883110
|View full text |Cite
|
Sign up to set email alerts
|

Retinol dehydrogenase 10 is indispensible for spermatogenesis in juvenile males

Abstract: Retinoic acid (RA), an active vitamin A derivative, is essential for mammalian spermatogenesis. Genetic studies have revealed that oxidation of vitamin A to retinal by retinol dehydrogenase 10 (RDH10) is critical for embryonic RA biosynthesis. However, physiological roles of RDH10 in postnatal RA synthesis remain unclear, given that Rdh10 loss-of-function mutations lead to early embryonic lethality. We conducted in vivo genetic studies of Rdh10 in postnatal mouse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
89
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 91 publications
(96 citation statements)
references
References 46 publications
2
89
0
1
Order By: Relevance
“…Data derived from developmental studies indicate that ALDH1A1 and ALDH1A3 are mostly active within tissues of ectodermal origin, i.e., the brain and eyes, whereas ALDH1A2 is more broadly present throughout the mesodermal tissues, including the gonad. Transcript and protein localization studies and global and conditional mouse mutants, which will be described in the following sections, have demonstrated a role for RDH10 and all three ALDH enzymes in the synthesis of RA within the testis Sugimoto et al 2012;Tong et al 2013;Vernet et al 2006b), yet there is significantly less known about which isozymes are expressed or essential for germ cell development in the fetal ovary. The current dogma suggests that RA acts in a paracrine manner: synthesized by one cell and then passed to a neighboring cell to induce a response .…”
Section: Testismentioning
confidence: 98%
“…Data derived from developmental studies indicate that ALDH1A1 and ALDH1A3 are mostly active within tissues of ectodermal origin, i.e., the brain and eyes, whereas ALDH1A2 is more broadly present throughout the mesodermal tissues, including the gonad. Transcript and protein localization studies and global and conditional mouse mutants, which will be described in the following sections, have demonstrated a role for RDH10 and all three ALDH enzymes in the synthesis of RA within the testis Sugimoto et al 2012;Tong et al 2013;Vernet et al 2006b), yet there is significantly less known about which isozymes are expressed or essential for germ cell development in the fetal ovary. The current dogma suggests that RA acts in a paracrine manner: synthesized by one cell and then passed to a neighboring cell to induce a response .…”
Section: Testismentioning
confidence: 98%
“…We and others have demonstrated that testicular RA mainly originates from Sertoli cells especially in puberty; however, it remains elusive whether the action of RA on spermatogonial differentiation is through germ cells or Sertoli cells, or both Sertoli and germ cells, as its receptors, RARs and RXRs, are expressed in both Sertoli cells and the undifferentiated spermatogonia (Gely-Pernot et al, 2012;Tong et al, 2013;Vernet et al, 2006b;Gaemers et al, 1998;DeFalco et al, 2015). For instance, genetic ablation of Rarg in germ cells resulted in only mild spermatogonial differentiation defects in mutants younger than one year old, indicating that either retinoid signaling in Sertoli cells is involved in spermatogonial differentiation, or that other subtypes of RARs in spermatogonia compensate for loss of RARγ function, as it is the case for many other developmental process (Gely-Pernot et al, 2012;Mark et al, 2009).…”
Section: Discussion Retinoid Signaling Directly Controls Spermatogonimentioning
confidence: 99%
“…For EdU labeling, as described previously (Tong et al, 2013), mice were i.p. injected with EdU (Invitrogen) (50 μg/g body weight) in PBS.…”
Section: Win18466 Ra Administration and Edu Labelingmentioning
confidence: 99%
“…An excellent model organ for the tissue-specifi c synthesis of at RA is the testis ( 28 ), as at RA synthesis within the testis is required for male fertility ( 29,30 ). For example, there is no initiation of spermatogenesis in mice which lack ALDH1A1, ALDH1A2, and ALDH1A3 in the Sertoli cells ( 30 ).…”
Section: Quantifi Cation Of Aldh1a1 Aldh1a2 and Aldh1a3 In Human Tementioning
confidence: 99%